Trust and Distrust in E-Commerce - Suk-Joo Lee (Sustainability, 2018)
Trust is the key ingredient for sustainable transactions. In the concept of trust, the trustor trusts the trustees. In e-commerce, the trustor is the buyer and the trustees are the intermediaries and the seller. Intermediaries provide the web-based infrastructure that enables buyers and sellers to make transactions. Trust is the buyer’s judgment and comprises two distinct concepts; both trust and distrust reside in the trustor. The purpose of this study was to examine the complicated effects of trust and distrust on a buyer’s purchase intentions. Previous studies have provided theoretical frameworks illustrating co-existent trust and distrust, trust transfers from one to another, and trust in buyer-intermediary-seller relationships. Based on these frameworks, this study (i) presented a holistic model that contained the judgment of buyers resulting in trust or distrust in the intermediary and the seller; (ii) investigated trust and distrust transfer from the intermediary to the seller, and (iii) explored the effects of various antecedents that affect trust and distrust. To validate the proposed model, we employed Partial Least Squares (PLS). A summary of key findings are as follows. First, buyer’s trust in an intermediary positively affected his or her trust in the seller, positively influencing purchase intention. In other words, we found the trust transfer from an intermediary to its seller. Second, distrust in an intermediary directly impacted on the buyer’s perceived risk, negatively influencing his or her purchase intentions. Third, structural assurance and perceived website quality of an intermediary gave a positive impact on buyer’s trust in the intermediary. The results of this study shed light on the necessity of managing both trust and distrust to facilitate sales in e-commerce.